Civic Dramaturgy and World-Making: Rehearsals of Meaning Cocreation - Ziakas, Vassilios (Tourism, culture & communication, 2025)
The drama enacted in communal settings of real life symbolically gives meaning to people and things shaping various public spheres and their world-making practices, thereby ultimately ordering the makeup of society. It does so, as it is omnipresent in social life and able to convert ideas to collective action through enunciations of embodied performances. Nevertheless, the nature, constitution, processes, and outcomes of social drama are poorly understood within the tourism and events scholarship, while there are no apparent links to Hollinshead's notion of worldmaking. Filling this gap, I delineate in this theoretical article the novel analytic framework of civic dramaturgy aimed at capturing the performative enactment of social drama as a semantic, narratological, and hermeneutic mode of symbolic action that enables the production of public spheres. Dramaturgy is seen as "civic" because it bears capacity for collective action, cocreating community conditions that make up people's lives. In parallel, I pinpoint interrelationships between civic dramaturgy and world-making. I then discuss how the civic dramaturgy lens is significantly enhanced by Hollinshead's refined conceptualization of worldmaking, concerned with the fluidity of less organized and power-driven forms of subjective becoming in touristic contexts. My approach regards world-making as a dramaturgic normalizing progression of imaginaries, histories, myths, and storylines creating or changing the ways in which things are understood symbolically and materially. I argue that the world-making imaginary adds to the dramaturgic repertoire with a spectrum of sites, subjects, places, and storylines, which view the world from certain standpoints but also tend to take on board different interpretations when they are performed as a result of the interaction between performances and audiences. Therefore, I suggest the adoption of a cross-fertilized "world-making dramaturgy" perspective as a multidimensional and post-disciplinary framework for the thorough analysis of social drama and its intersections with the production of public spheres. For conceptual clarity, I note that I intentionally use the spelling "world-making" with the hyphen denoting the distinction of the two conceptual spheres (world and making), and the variable outcome arising from their dramaturgic performance.